2014
DOI: 10.1161/atvbaha.114.303896
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol Promotes Adipocyte Hypertrophy and Adipose Tissue Inflammation in Visceral, but Not in Subcutaneous, Fat in Monkeys

Abstract: Objective Excessive caloric intake is associated with obesity and adipose tissue dysfunction. However, the role of dietary cholesterol in this process is unknown. The aim of this study was to determine whether increasing dietary cholesterol intake alters adipose tissue cholesterol content, adipocyte size, and endocrine function in nonhuman primates. Approach and Results Age-matched, male African Green monkeys (n=5 per group) were assigned to one of three diets containing 0.002 (Lo), 0.2 (Med) or 0.4 (Hi) mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
2
32
2
Order By: Relevance
“…They raise the question as to whether the findings obtained in mouse studies can be directly extrapolated to other mammalian species. Despite the finding that inflammation can also lead to metabolic impairment in other mammalian species (Basinska et al 2015), only a limited number of comparative studies of non-human primates and canines has explored the metabolic impact of adipose tissue inflammation (Chung et al 2014;Castro et al 2015;Bastien et al 2015). Thus, whether adipose tissue hosts immune cells in mammals other than rodents and primates and whether these immune cells have the ability to regulate metabolism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They raise the question as to whether the findings obtained in mouse studies can be directly extrapolated to other mammalian species. Despite the finding that inflammation can also lead to metabolic impairment in other mammalian species (Basinska et al 2015), only a limited number of comparative studies of non-human primates and canines has explored the metabolic impact of adipose tissue inflammation (Chung et al 2014;Castro et al 2015;Bastien et al 2015). Thus, whether adipose tissue hosts immune cells in mammals other than rodents and primates and whether these immune cells have the ability to regulate metabolism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the studies addressing the role of the SVF cells has been conducted in murine models of human diseases, in clinical studies, or in non-human primates (Chung et al 2014;Greenberg and Obin 2006) and thus, we lack information on the nature and the functions of the SVF in other mammals. Only a negligible number of studies have been carried out on SVF stem cells (Marx et al 2015) and we have no information on the immune phenotype of the SVF outside of rodents and primates.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol elicits a strong macrophagedriven inflammatory response in the arterial wall and adipose tissue [21,22]. Recent evidence now also point to an association between the gut and cholesterol metabolism [23].…”
Section: Lipid Alterations During Nash Pathogenesismentioning
confidence: 99%
“…To directly address the effect of dietary cholesterol on adipocyte properties, Chung and colleagues fed male African Green monkeys diets of low, medium or high cholesterol 34 . The authors found that with increasing dietary cholesterol content, free cholesterol and adipocyte size increased in parallel in visceral but not subcutaneous fat.…”
Section: Obesity and Lipid Metabolismmentioning
confidence: 99%